Language proficiency, education, and language attitudes in Skolt Sami communities between the 1850s and 2020s - Valtonen, Taarna; Juutinen, Markus (Suomalais-Ugrilainen Seura, 2026)
In this article, we describe the changes in language skills, education, and language attitudes of the Skolt Sami between the 1850s and 2020s and analyze the reasons for these changes. The description and analysis are based on an in-depth reading and interpretation of existing older sources and present-day interviews. The Skolt Sami territories are divided between three countries: Russia, Norway, and Finland. Since the nineteenth century these territories have been increasingly colonized by members of the majority cultures, but also by several linguistic and cultural minorities. Due to this, the Skolt Sami have been a highly multilingual people and have known, in addition to their own language, one or more often several languages. Their language proficiency has varied according to their language contacts. For a long time, the Skolt Sami communities saw multilingualism as a positive value, as it helped individuals to cope in varying situations and contexts. The same ideology was dominant in connection to the value given to schooling and education in general, even though this was only available in majority languages. However, practical obstacles to education during and after elementary education were often perceived. From World War II, and in Norway even before, language attitudes began to change rapidly and the nationalistic ideal of monolingualism started to gain ground. To learn other, larger languages was viewed as more important than knowing Skolt Sami. This was caused by forced assimilation, which was practiced especially in schools from the early twentieth century on, and by negative attitudes of the majority populations, especially peer groups. Since the late twentieth and early twenty-first century language attitudes have started to change yet again, and an active language revitalization process has started. At present, schools and other educational institutions have become one of the most important actors in processes of language revitalization.
Readjustment: reactions to societal change in Finno-Ugric minority language communities